تحليل الصراع الباطني للشخصية الرئيسية في رواية الحب الضائع لطه حسين (الدراسة سيكولوجي الأدب) - Qurrotu Ma’wa, Utia; Farma, Tri Wi (Journal of Arabic Language and Literature (ALLAIS), 2023)
The novel Al-Hubb Adh-Dhaa'i by Thoha Husein is one of the contemporary literary works that is full of psychological aspects. The novel describes human daily life with all its problems, especially love and inner conflict experienced by the main character. The purpose of this study is to find out, describe and analyze the inner conflict of the main character in the novel Al-Hubb Adh-Dhaa'i by Thoha Husein. This research is a qualitative research with a descriptive approach. Data collection is done by using documentation technique while the validity of the data is done by using theory triangulation technique. Data analysis used content analysis method, namely by taking the essence of an idea or information and then drawn it into a conclusion. The results of this study are the emergence of several problems experienced by the main character that caused his psyche to be shaken. The forms of inner conflict experienced by the main character include depression, obsession, anxiety, fear, insecurity, guilt, inadequacy, frustration, anger, hurt, and dissatisfaction, and attention